Is there a Good Moral Argument against Moral Realism? - Golub, Camil (Ethical theory and moral practice, 2021)
It has been argued that there is something morally objectionable about moral realism: for instance, according to realism, we are justified in believing that genocide is wrong only if a certain moral fact obtains, but it is objectionable to hold our moral commitments hostage to metaphysics in this way. In this paper, I argue that no version of this moral argument against realism is likely to succeed. More precisely, minimal realism―the kind of realism on which realist theses are understood as internal to moral discourse―is immune to this challenge, contrary to what some proponents of the moral argument have suggested, while robust non-naturalist realists might have good answers to all versions of the argument as well, at least if they adopt a certain stance on how to form metaphysical beliefs in the moral domain.